PENGALAMAN MUSIK DALAM KEGIATAN PADUAN SUARA DI SMPN 1 PAYAKUMBUH - Aprilla Hel Susana; Ardipal Ardipal; Yos Sudarman (FBS Universitas Negeri Padang, 2015)
Abstract This article aims to explain the Experience Music in Choral Activities at SMP Negeri 1 Payakumbuh. Qualitative research with descriptive method that provides a complete picture and set forth in writing in the event of Experience Music Choir at SMP Negeri 1 Payakumbuh. Research conducted the 1st half of the school year 2014/2015. The data obtained were collected through observation, interviews, documentation and study the literature. Data analysis included the presentation of data and inference data. Research explains that the Music Experience Choir Activity in SMP Negeri 1 Payakumbuh showed that activity in class VIII9 choir has advantages and disadvantages, so only a little musical experience gained by the students. The results of extracurricular activities chorus make students more aware of and understand the vocal technique, the students gained experience more in terms of both theory and practice. Interrelationship between choral activities in class VIII9 with extracurricular activities choir, where students who participate in extracurricular activities choir has more musical experience than those who did not follow extracurricular activities. Keywords: Experience music and choral activities.